The Role of Village Government in the Management and Protection of Mangrove Ecosystems in the Bangka Belitung Islands Province : A Comparative Study in Rebo Village, Kota Kapur Village and Kotawaringin Village, Bangka Regency - Aysyah, Nur; Tsabitah, Zalfa Haza; Febyana, Nyimas Dwi; Hidayat, Novendra (Journal of Social and Policy Issues, 2025)
This study aims to analyze the role of village governments in the management and protection of mangrove ecosystems in Bangka Regency and to formulate a model for community-based sustainable governance based on blue economy principles. The study employed a descriptive qualitative approach with a multiple-case design in three villages: Rebo Village, Kota Kapur Village, and Waringin Village, representing different stages of mangrove management. Data collection was conducted through in-depth interviews, participant observation, and documentation studies. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing. The results show that the role of village governments varies significantly and is influenced by institutional capacity and external support. Waringin Village is in the early stages, with conservation activities still dependent on external parties. Kota Kapur Village implements a participatory model through collaboration with community groups. Meanwhile, Rebo Village has reached the institutional stage with multi-actor partnership-based mangrove ecotourism management. Key success factors include adaptive local leadership, community participation, regulatory support, and cross-sector partnerships. This study concludes that the role of village government evolves through three stages: initiative, participatory, and institutional, with a balance of regulatory, facilitative, and collaborative functions as key. Integrating mangrove conservation with principles of the blue economy is a crucial strategy for sustainable coastal development.